Sustained antibiotic release from biodegradable gelatin–silica hybrid for orthopedic infections - Lin, Yu-Chien (2024)
Antibiotic-loaded polymethylmethacrylate (PMMA) beads are commonly employed to treat prosthetic joint infections (PJI) and chronic osteomyelitis due to their excellent mechanical strength. However, PMMA's non-degradability results in a burst release of antibiotics and potential renal toxicity, necessitating additional surgeries for bead removal. There is a critical need for infection control materials that can deliver antibiotics effectively, maintain adequate mechanical strength, and degrade uniformly. This study introduces a gelatin–silica hybrid antibiotic carrier, characterized by covalent bonds between the gelatin and silica networks. The incorporation of the silica network enhances the compressive strength to 32.53 ± 2.4 MPa and ensures uniform degradation over 6 months, aligning with clinical timelines. Furthermore, the gelatin–silica hybrid can support up to 10 wt% antibiotic loading without compromising its properties, making it a promising candidate for next-generation infection control materials.